Copper-catalyzed trifluoromethylation of alkenes: synthesis of trifluoromethylated benzoxazines1. Issue 31 (21st August 2015) - Jana, Sadhan; Ashokan, Athira; Kumar, Shailesh; Verma, Ajay; Kumar, Sangit
<x xml:space="preserve">Abstract</x> A ligand and base free copper catalyzed method has been developed for the construction of trifluoromethylated benzoxazines by using Umemoto's reagent.